PERAN PERGURUAN TINGGI DALAM IKUT MENGATASI PENGANGGURAN TERDIDIK - Mudzakir, Mudzakir (Potensio, 2013)
Unemployment (including unemployment educated) give a negative impact to the community and economy of the State. So that negative impacts do not occur, then the necessary action to resolve them. Many government policies have been published and one of them is the implementation of Concept Based Curriculum in college. Institutions of higher education as an operator in the implementation of Competency Based Curriculum. But it is still a bit that has done it. Among those who turned out to be not implemented fully. A limited resource constraints. So the government gives grants based Curriculum Competition began in 2013. If the Competency-Based Curriculum concept can be implemented in full and by all higher education institutions in Indonesia, the increase in the number of educated unemployed can be resolved. Therefore, implementation of the concept of curriculum-based curriculum in higher education institutions is a form of concrete role of higher education in addressing the increasing number of educated unemployment is very important.Â Keywords: Unemployment, Competency-Based Curriculum, Higher Education